1991
DOI: 10.1016/0014-5793(91)80820-s
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of troponin I isoforms in fetal human heart

Abstract: We have used antibodies specific for troponin I proteins to examine human cardiac development and have detected a transiently expressed developmental isoform. This isoform is distinct from adult cardiac troponin I (TnIc) but is indistinguishable, on the basis of electrophoretic mobility and antibody reactivity, from the isoform found in slow skeletal muscle (TnIs). Furthermore, we show that mRNA for TnIs is present in fetal. but not adult, heart. Analysis of a developmental series of fetal samples indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…[18, 47, 48] Importantly, Metzger and colleagues have shown that the troponin complex in human iPSC-CMs are comprised largely of ssTnI even after 9 months of culture. [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18, 47, 48] Importantly, Metzger and colleagues have shown that the troponin complex in human iPSC-CMs are comprised largely of ssTnI even after 9 months of culture. [49].…”
Section: Resultsmentioning
confidence: 99%
“…[18, 47] According to our Western analysis, culturing iPSC-CMs on 4%PEG-96%PCL for 30 days dramatically increased cTnI:ssTnI ratio to approximately 70:30, which was not achieved in human iPSC-CMs even after 9 months of culture. [18, 47] Immunostaining with cTnI suggests that the increase in cTni:ssTnI ratio may reflect a ssTnI to cTnI switch in a subset of iPSC_CMs maintained on 4%PEG-96%PCL. Finally, the fraction of cells that expressed MLC-2v was about 5-fold higher for 30-day old iPSC-CMs maintain on 4%PEG-96%PCL than for 100-day old iPSC-CMs maintained on traditional substrates like Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…In this light, we propose that the developmentally controlled and irreversible genetic switch in the sarcomeric TNNI genes provides an excellent marker to track the differentiation status of stem cell-derived cardiac myocytes. Owing to strict developmental control in all mammalian hearts, including humans, the programmed inactivation of the “fetal” TNNI gene product, ssTnI, together in exquisite temporal concert with stoichiometric replacement by the adult gene product, cTnI, represents a unique molecular marker of cardiac myocyte maturation status (Bhavsar et al., 1991). …”
Section: Discussionmentioning
confidence: 99%
“…The cardiac troponin I is unique to cardiac muscle. The skeletal muscle, both in experimental animals and humans, does not express cardiac troponin I at any developmental stage or reexpress it in response to any pathological stimuli [30, 31, 32, 33, 34]. Therefore, cardiac troponin I was reported to be very specific in chronic renal failure, especially with the monoclonal antibody assay that does not cross-react with the skeletal muscle isoform [27, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Since cardiac troponin I is exclusively of cardiac origin and, unlike creatine kinase-MB isoenzyme and cardiac troponin T, does not express in the skeletal muscle at any developmental stage [30, 31, 32, 33, 34], it has been shown to be more specific for the detection of myocardial injury in chronic renal failure patients [21, 22, 23, 29]. However, there are very few well-controlled studies evaluating the specificity of cardiac troponin I and creatine kinase-MB isoenzyme in ambulatory asymptomatic chronic renal failure patients on long-term hemodialysis, and evaluating the effect of hemodialysis on serum levels of cardiac troponin I and creatine kinase-MB isoenzyme.…”
Section: Introductionmentioning
confidence: 99%